The influence of work motivation and compensation on employee performance PT. Bank mega, Tbk Bandung Main Branch Office Personal Card and Load Officer Division - Tarmidi, Didi; Sukandar, Wildan Aji Firdaus (Technium Social Sciences Journal, 2021)
This research was conducted to analyze the influence of work motivation and compensation on the performance of employees of PT Bank Mega, Tbk Bandung Main Branch Office Personal Card, and Loan Officer Division. Employee Performance is researched to create a work ecosystem that can improve employee performance and company performance to consumers. In this study, the sample used was employees of the Personal Card and Loan Officer Division as many as 36 respondents. Multiple linear regression analysis methods are used to partially and simultaneously find an influence on employee performance variables processed using SPSS 25 for Windows software. The main data from the study used questionnaire surveys, and secondary data was obtained through journal publications, articles, and theory books. These results showed the researchers that two free variables yaoti work motivation (X1) and compensation (X2), had a significant influence on the performance of employees at PT Bank Mega, Tbk Bandung Main Branch Office Personal Card, and Loan Officer Division.